Implementasi Jaringan VPN Menggunakan L2TP Dengan IP Sec Pada PT Datindo Infonet Prima - Farizal Triyansa; Irwan Agus Sobari (LPPM Universitas Bina Sarana Informatika, 2022)
This design is based on the need for a network that specializes in users for working at home (WFH) due to the covid-19 pandemic problem by PPKM level 3 government regulations. using public facilities. With a VPN, companies can establish an easy and secure data connection. VPN can allow for the formation of a private data network that can be accessed through a public network, namely the internet, only those who have the authority can access the VPN. L2TP (Layer 2 Tunneling Protocol) offers a fairly good security solution by creating a tunnel on a public network. The use of L2TP itself cannot be separated from the influence of the security system which is growing rapidly. Therefore, by adding the L2TP process with IPsec, it is hoped that it will be able to handle problem cases from the network security system. With VPN access, workers can work from home (WFH) without having to go to the office.